Measured versus self-reported body height and body mass in patients after an acute coronary syndrome - Domagała, Zygmunt; Kałka, Dariusz; Kurc-Darak, Bożena; Womperski, Krzysztof; Rusiecki, Lesław; Krauz, Ewa S.; Gworys, Bohdan; Dąbrowski, Paweł (Anthropological Review, 2017)
The basic anthropometric data describing a person in the broadest context are body weight and height, two of the most frequently analyzed somatometric parameters. The same is true I in relation to clinical patients. The aim of the present study was to compare the self-reported and actual body weight, height and BMI in patients suffering from coronary artery disease and undergoing cardiac rehabilitation. The study sample consisted of 100 patients treated for coronary artery disease. The patients were asked to state their body weight and height. At the same time a three-person study team took measurements, which were later the basis for verification and objective assessment of the data provided by the patients. Statistical analysis was performed with Statistics 11.0 PL software. The analysis of mean results for the assessed group of patients has shown the presence of statistically significant differences between declared and actual data. The differences were observed for both male and female study population. It has been proven that the subjects declare greater body height (mean value 1.697 m vs. 1.666 m) and lower body weight (80.643 kg vs. 82.051 kg). Based on the data from surveys and direct measurements, the body mass index for the self-reported and actual data was calculated. A comparison of these values has shown considerable statistically significant differences. The differences between declared and actual data point to highly subjective self-assessment, which disqualifies the declared data in the context of monitoring of treatment and rehabilitation processes. The authors believe that actual data should be used in direct trial examination of patients suffering from coronary artery disease who presented with acute coronary syndrome.